Penerapan Model Pembelajaran Inkuiri untuk Meningkatan Hasil Belajar Mahasiswa pada Perkuliahan Dinamika Sistem - nurwulan fitriyanti (Journal of Teaching and Learning Physics, 2019)
The purpose of this research is to find student learning outcome by applying the inquiry learning model for System Dynamic subject. The research method in the form of Classroom Action Research which is done in 2 cycles and 3 meetings for every cycle. In this research, the samples are 43 students of the Department of Engineering Physics, Telkom University, which become sample of this research.  Student cognitive learning outcomes data were obtained through description tests, while affective and psychomotor learning outcomes data were obtained through observation sheets. The results obtained from this study, in the form of cognitive learning outcomes of students using inquiry learning models, are N-Gain values of 0.52 in the first cycle and 0.45 in the second cycle. Whereas for affective learning outcomes, there was an increase in the average results per class, from 85% in the first cycle to 93% in the second cycle. The same thing for the psychomotor aspect, the class average in the first cycle was 81% and in the second cycle increased to 88%. Based on the results obtained in the study, it can be concluded that the application of the inquiry learning model has an influence on improving student learning outcomes.